UPAYA MEWUJUDKAN GENERASI MUDA BEBAS NARKOBA MELALUI SOSIALISASI DAN SKRINING NARKOBA DI SMP N 9 PALEMBANG - Evi Lusiana (Lembaga Pengabdian pada Masyarakat, 2020)
Efforts to achieve a drug abuse-free young generation through socialization and drug abuse screening at student junior high schools (SMP) is very important because the junior high school students are the next generation who determine the fate of the nation. One such effort is the extension lecture and video animation. This community service aims to improve the knowledge of the dangers of drug abuse in the young generation, especially students in junior secondary school 9 Palembang. The program has shown an improvement of knowledge about definition, classification, impact and drug abuse prevention in the young generation.